2020
DOI: 10.3390/pathogens9030191
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-acetyltyramine-O,β-glucuronide in Persons with Onchocerciasis-Associated Epilepsy

Abstract: We investigated urinary N-acetyltyramine-O,β-glucuronide (NATOG) levels as a biomarker for active Onchocerca volvulus infection in an onchocerciasis-endemic area in the Democratic Republic of Congo with a high epilepsy prevalence. Urinary NATOG was measured in non-epileptic men with and without O. volvulus infection, and in O. volvulus-infected persons with epilepsy (PWE). Urinary NATOG concentration was positively associated with microfilarial density (p < 0.001). The median urinary NATOG concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Onchocerciasis elimination efforts, which lead to reductions in microfilarial prevalence and load, have been shown to decrease the incidence of epilepsy/NS [78,79]. Recent studies in the DRC showed that high seizure frequency was associated with increasing microfilarial density [71] and increasing levels of urinary N-acetyltyramine-O,β-glucuronide (NATOG), a biomarker for onchocerciasis [90]. Furthermore, a randomized trial in the DRC, comparing a single versus a multiple dose of ivermectin treatment regimen in O. volvulus-infected persons with epilepsy treated with phenobarbital showed that the multiple dose ivermectin regimen was associated with a reduced frequency of seizures [91].…”
Section: Biological Gradient (Dose Response)mentioning
confidence: 99%
“…Onchocerciasis elimination efforts, which lead to reductions in microfilarial prevalence and load, have been shown to decrease the incidence of epilepsy/NS [78,79]. Recent studies in the DRC showed that high seizure frequency was associated with increasing microfilarial density [71] and increasing levels of urinary N-acetyltyramine-O,β-glucuronide (NATOG), a biomarker for onchocerciasis [90]. Furthermore, a randomized trial in the DRC, comparing a single versus a multiple dose of ivermectin treatment regimen in O. volvulus-infected persons with epilepsy treated with phenobarbital showed that the multiple dose ivermectin regimen was associated with a reduced frequency of seizures [91].…”
Section: Biological Gradient (Dose Response)mentioning
confidence: 99%
“…Recently, Hotterbeekx et al [ 16 ] conducted a further study on the viability of NATOG as a biomarker for onchocerciasis. The mean amounts of NATOG were elevated in infected (9.7 ± 1.4 µM, n = 117) compared with non-infected individuals (3.2 ± 0.9 µM, n 55).…”
Section: Discussionmentioning
confidence: 99%
“…1 a). In Table 6 of their manuscript, Hotterbeekx et al [ 16 ] compiled the results of NATOG measurements in urine samples of the previous studies. The maximal amounts of NATOG in samples of all non-infected individuals, of all Mp-infected and Ll + Mp-infected individuals was < 80 µM (the only exception being Ll-infected), while the groups of O. volvulus -infected individuals (Ov and co-infection; Ov infection with/without epilepsy) contained data points with NATOG levels > 80 µM [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with OAE were selected among participants from previously described studies in South Sudan [ 27 ] and the DRC [ 28 ]. Characteristics of the study participants are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%